The effect of overlap length adhesive with bonded in Z type materials - Işcan, Bahattin; Adin, Hamit; Turgut, Aydin (My University, 2011)
The usage of adhesives as connecting method is increasing rapidly in today world. Many of research, development and engineering have been made to find the most important parameters of adhesion. In this study, stress analysis of bonded Z type that connected with various adhesives has been investigated. The adhesive thickness and overlap non-angle was constant but overlap length and overlap angle were varied. This paper has deal with the effect of overlap length on predicting of failure load of adhesive. An effective method for numerical solution in finite element method (FEM) has been performed in analysis. The FEM code employed was ANSYS(10.0). Experimental results were compared with numerical results and were found quite reasonable. ©2011 Academic Journals.
Keywords: Adhesive; Finite element method (FEM); Interface; Stress analysis